2008
DOI: 10.1142/s0217751x08039761
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model of Inverted Neutrino Mass Hierarchy and Resonant Leptogenesis

Abstract: We present a new realization of inverted neutrino mass hierarchy based on S 3 × U (1) flavor symmetry. In this scenario, the deviation of the solar oscillation angle from π/4 is correlated with the value of θ 13 , as they are both induced by a common mixing angle in the charged lepton sector. We find several interesting predictions: θ 13 ≥ 0.13, sin 2 θ 12 ≥ 0.31, sin 2 θ 23 ≃ 0.5 and 0 ≤ cos δ ≤ 0.7 for the neutrino oscillation parameters and 0.01 eV < ∼ m ββ < ∼ 0.02 eV for the effective neutrino mass in neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Such a scenario has been termed 'resonant leptogenesis', and has benefited from many studies in different formalisms 21 [61,82,85,131,132,184,189,[234][235][236][237][238][239][240][241][242][243][244]. As this review focuses on hierarchical N i , we briefly list the idea and some references.…”
Section: Resonant Leptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario has been termed 'resonant leptogenesis', and has benefited from many studies in different formalisms 21 [61,82,85,131,132,184,189,[234][235][236][237][238][239][240][241][242][243][244]. As this review focuses on hierarchical N i , we briefly list the idea and some references.…”
Section: Resonant Leptogenesismentioning
confidence: 99%
“…It is a theoretical challenge to construct models where a mass splitting as small as the decay width is naturally achieved. For attempts that utilize approximate flavour symmetries see, for example, [189,237,239,243,246], while studies of this issue in the framework of minimal flavour violation can be found in [131,132,244].…”
Section: Resonant Leptogenesismentioning
confidence: 99%
“…For a quasi-degenerate spectrum instead all the discussion changes because in this case the self-energy diagram involving several triplets, figure 2, becomes resonant, through the propagator of the virtual triplet (for references on resonant leptogenesis in the type-I model, see e.g. [46][47][48][49][50][51][52][53][54][55][56][57][58]). With several fermion triplets the CP-asymmetry of, say, 1 , takes the form [7]…”
Section: Resonant Case: Multiple Fermion Triplets With Quasi-degeneramentioning
confidence: 99%
“…[6]. This approach enables one to relate the CP violating phase δ (appearing in the neutrino oscillations) with the cosmological CP asymmetry [6][7][8][9][10][11][12][13][14][15]. Especially attractive looks the setup with two (or more) quasi-degenerate RHN's [9][10][11][12]15] because, besides the further reduction of the model parameter number, it offers the possibility for resonant leptogenesis [16][17][18] (for recent discussions on resonant leptogenesis see [19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%